Infective endocarditis of a bicuspid aortic valve complicated by septal aneurysm and mitral-aortic intervalvular fibrosa pseudoaneurysm - Hicaz Zencirkıran Ağuş; Oya Atamaner; Begüm Uygur; Ali Kemal Kalkan; Mehmet Ertürk (KARE Publishing, 2018)
Aortic valve endocarditis can lead to the destruction or perforation of the leaflets, ring abscess, fistula, or perivalvular regurgitation; less commonly, the regurgitation itself may result in secondary damage to subaortic structures. Pseudoaneurysm of the mitral-aortic intervalvular ﬁbrosa is a rare complication of native aortic valve endocarditis. This region is a relatively avascular area and is prone to endocarditis infection and subsequent aneurysm formation. Herein, the case of a 33-year-old man who was diagnosed with bicuspid aortic valve endocarditis complicated by a pseudoaneurysm, an aneurysm, and aortic valve rupture is described.